The Draft Genome of a Hydrogen-producing Cyanobacterium, Arthrospira platensis NIES-46 - Suzuki, Shigekatsu (J Genomics, 2019)
Arthrospira is an economically important cyanobacterium that contains many useful products, including proteins, vitamins, lipids, and pigments, and it is distributed in several alkaline soda lakes. Arthrospira platensis NIES-46 produces large amounts of hydrogen. In this study, we sequenced the NIES-46 draft genome and performed comparative analyses among Arthrospira species to elucidate the genomic background of this strain. The genome consists of 5.7 Mbp with a GC% of 44.5% and encodes 5,008 proteins. Our phylogenetic analysis using multiple orthologous proteins shows that Arthrospira is divided into two clades and that NIES-46 is closely related to A. platensis NIES-39. The genome structure and protein functions are highly conserved between A. platensis NIES-39 and NIES-46, suggesting that these two strains have recently diverged. Genes involved in hydrogen production are well-conserved among Arthrospira species, indicating conserved abilities to produce hydrogen.